Sobre el discutido significado de algunas expresiones proverbiales de Herodas - José Antonio Fernández Delgado (Exemplaria Classica, 2010)
As a conclusion to two previous papers on Herodas' proverbs, this time we deal with other proverbial expressions which are equally controversial and have not been properly discussed yet. Our main objective is to clarify their meaning and usage.